2022
DOI: 10.21037/jtd-22-1457
|View full text |Cite
|
Sign up to set email alerts
|

Screening of atrial fibrillation diagnostic markers based on a GEO database chip and bioinformatics analysis

Abstract: Background: Study have shown that atrial fibrillation (AF) is a disease with genetic risk, and its pathogenesis is still unclear. This study sought to screen the gene microarray data of AF patients and to perform a bioinformatics analysis to identify AF signature diagnostic genes. Methods:The AF gene sets from the Gene Expression Omnibus (GEO) database were screened, and the differentially expressed genes (DEGs) were identified after the normalization of the data set by R software.We conducted a gene set enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…By the CIBERSORT algorithm, we found that T cells and macrophage subpopulations showed high variability between AF and SR groups. In addition, consistent with previous findings, 49 M2 macrophages and T cells were increased in the AF group. The new study demonstrated a higher infiltration abundance of the M2 typical marker CD163 in the LAA of patients with AF by quantitative analysis.…”
Section: Discussionsupporting
confidence: 92%
“…By the CIBERSORT algorithm, we found that T cells and macrophage subpopulations showed high variability between AF and SR groups. In addition, consistent with previous findings, 49 M2 macrophages and T cells were increased in the AF group. The new study demonstrated a higher infiltration abundance of the M2 typical marker CD163 in the LAA of patients with AF by quantitative analysis.…”
Section: Discussionsupporting
confidence: 92%
“…They were GPR22, COG5, GALNT16, OTOGL, and MCOLN3. Potential circRNA such as has_circ_0006314 and hsa_circ_0055387 were also shown to be biomarkers for postoperative AF, and immune genes such as CHGB, HLA-DRA, LYZ, IGKV1-17, and TYROBP were upregulated [ 52 ]. In addition, macrophages, mast cells, and neutrophils were significantly infiltrated in left atrial tissue [ 53 ].…”
Section: Inflammation and Immune Systemmentioning
confidence: 99%
“…Empirical evidence found that high blood pressure, diabetes, tobacco usage, and alcohol consumption stand as pivotal risk factors in the development of atrial brillation (3). In addition, genetic factors assume a noteworthy role in the onset and progression of AF (4). In ammation and atrial brosis are the basic mechanisms of the pathophysiological process of the occurrence and development of atrial brillation (5).…”
Section: Introductionmentioning
confidence: 99%